A piece of Renaissance furniture in the church of St. Cunera at Rhenen (Bulletin KNOB, 1991)
The subject of this article is a piece of Renaissance furniture in the (at present Dutch Reformed) church of St. Cunera at Rhenen. The design and details show this furniture to be a companion piece to the choir-stalls that are still in situ. The stalls are dated 1570 and probably were made in the city of Utrecht.The nowadays saet stands in the southern transept, but obviously that was not its original position. It is usually referred to as the 'so-called bishop's throne', but it is unlikely that the seat ever had that function. There are no grounds to assume that a parish church like St. Cunera had a bishop's throne or cathedra. In addition, the piece is far too large for one person, it lacks either an episcopal coat-of-arms or mitre, and only with great difficulty the liturgically correct northern side of the altar could have been placed on.The southern side of the (now lost) altar offers enough space to accomodate the piece. A seat on that side of the chancel would be a sedilia. Late Medieval sedilia usually consisted of a tripartite structure under a canopy, because they were intended for the officiating priest, deacon and subdeacon. The width of the Rhenen seat (189 cm) would be ideal to accomodate three fully vested clergymen, but it lacks the tripartite structure, except in the interior decoration of the canopy.The panelling on the seat back however does not refer to a division into individual seats. The same holds true for the panelling on the back of the stalls. These features can be explained as characteristic of Renaissance design. Apart from stalls and sedilia, St. Cunera's still has its rood loft, which usually is dated (on stylistic grounds) ca. 1550-1555.New archival material sheds some light on the liturgical context of these furnishings. The Teutonic Knights were the patrons of St. Cunera's from the 1270's and they provided for clergy to serve the parish. By the fifteenth century their duties included the daily singing of the service and the celebration of high mass at the main altar as well. There is evidence that during the 1560's and 1570's four vicars, a chaplain, a sexton, a schoolmaster and six choir boys regularly sang the full seven-fold Bénédictine service, which from the late Middle Ages onwards was sung in many non-collegiate churches.What makes the sedilia interesting is not only their elegance and craftmanship. They are probably the only surviving wooden pre-Reformation sedilia in the Netherlands. What is more, these sedilia, and the stalls to which they belong, are still in the church for which they were made.